2018
DOI: 10.1002/ep.12915
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced adsorption capacity and selectivity toward inorganic and organic mercury ions from aqueous solution by dye‐affinity adsorbents

Abstract: Adsorption of inorganic mercury [Hg(II)] and organic methylmercury [MeHg(II)] ions onto dye‐affinity agrowaste (dye‐AW) was investigated. The dye‐affinity adsorbents were prepared by the chemical‐thermal reaction between the agrowaste (AW) and dye solutions [i.e., Reactive Red 120 (RR), Reactive Black B (RB), Methylene Blue (MB), and Methyl Orange (MO)] under an alkaline condition. An almost perfect removal of Hg(II) was observed for all adsorbents, while for MeHg(II), the dye‐affinity adsorbents have a higher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Pristine 8 behaved as hexadentate ligands to coordinate with Hg 2+ by oxygen and nitrogen atoms to form a feasible chelating complex (Figure ). , The plausible adsorption mechanism demonstrated that Hg 2+ was successfully adsorbed by the coordination interactions, electrostatic, and Lewis’s acid–base interactions between Hg 2+ and oxygen/nitrogen-bearing functional groups of 8 . In addition, Hg 2+ might have been adsorbed within pores present on the surface of 8 via electrostatic interactions with oxygen-containing functional groups of 8 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pristine 8 behaved as hexadentate ligands to coordinate with Hg 2+ by oxygen and nitrogen atoms to form a feasible chelating complex (Figure ). , The plausible adsorption mechanism demonstrated that Hg 2+ was successfully adsorbed by the coordination interactions, electrostatic, and Lewis’s acid–base interactions between Hg 2+ and oxygen/nitrogen-bearing functional groups of 8 . In addition, Hg 2+ might have been adsorbed within pores present on the surface of 8 via electrostatic interactions with oxygen-containing functional groups of 8 (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…A similar plausible adsorption mechanism of Hg 2+ on the different adsorbents was also investigated . The thermodynamic measurements and related parameters are presented in Table S4.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Adsorption of inorganic mercury [Hg(II)] (and organic methylmercury [MeHg(II)]) onto dye-affinity agrowaste (dye-AW) was investigated [90]. The dye-affinity adsorbents were prepared by the chemical-thermal reaction between the agrowaste (AW) and dye solutions (i.e., reactive red 120 (RR), reactive black B (RB), methylene blue (MB), and methyl orange (MO)) under alkaline medium.…”
Section: 6-diaminopyridine (Pd) and Polyamine Compoundsmentioning
confidence: 99%